2018
DOI: 10.1016/j.amjcard.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Canakinumab to Improve Exercise Capacity in Patients With Long-Term Systolic Heart Failure and Elevated C-Reactive Protein

Abstract: Interleukin-1β (IL-1β) is a cytokine involved in atherothrombosis and is known to depress cardiac function. We hypothesized that blocking IL-1β in patients with symptomatic systolic heart failure (HF) would improve their cardiorespiratory fitness. The purpose of the study was to measure changes in peak oxygen consumption (VO) in 30 patients with prior myocardial infarction, high-sensitivity C-reactive protein ≥ 2 mg/l and HF with left ventricular ejection fraction (LVEF) < 50% enrolled in the Canakinumab Anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…The link between inflammation and heart failure is discussed for more than 2 decades [26,27]. In accordance to our findings, a recent subgroup analysis of the CANTOS trial described improved outcomes in patients with CHD and heart failure after anti-inflammatory-therapy with Canakinumab [28]. In the meantime, there is numerous evidences suggesting that activation of the innate and adaptive immune system plays a critical role in pathogenesis and maintenance of heart failure, various cytokines and chemokines were described as supportive evidence in this content [29,30].…”
Section: Discussionsupporting
confidence: 89%
“…The link between inflammation and heart failure is discussed for more than 2 decades [26,27]. In accordance to our findings, a recent subgroup analysis of the CANTOS trial described improved outcomes in patients with CHD and heart failure after anti-inflammatory-therapy with Canakinumab [28]. In the meantime, there is numerous evidences suggesting that activation of the innate and adaptive immune system plays a critical role in pathogenesis and maintenance of heart failure, various cytokines and chemokines were described as supportive evidence in this content [29,30].…”
Section: Discussionsupporting
confidence: 89%
“…Recent results from the CANTOS study showed that anti-inflammatory therapy with canakinumab, a therapeutic monoclonal antibody targeting IL-1β, resulted in reduced rate of recurrent atherosclerotic cardiovascular events in post-infarct patients with CRP ≥ 2 mg/L, especially in patients with greater CRP reduction, even in the absence of lipid lowering [39,40]. The findings of small prespecified secondary analysis of CANTOS may also indicate a positive impact of canakinumab on long-term LVEF in patients with post-infarct systolic HF [41]. CANTOS also provided proof of concept evidence in humans that modulation of the IL-6 signaling pathway-at least with canakinumab-is associated with reduced cardiovascular event rates [42].…”
Section: Discussionmentioning
confidence: 97%
“…Gaining a better understanding of the relationship between CRP and cardiac function in patients who have undergone radiation therapy could potentially help to optimize treatment, and ideally, serve as therapeutic targets to minimize long-term unwanted cardiac side-effects. IL-1 blockers are being studied for the prevention and treatment of heart failure, showing a promising safety and efficacy profile [30][31][32][33][34][35] thus introducing the possibility of future clinical trials investigating IL-1 blockade to treat patients at risk for radiation-induced heart failure. Abbreviations Δ: Delta; E: Early transmitral velocity; e': Early diastolic mitral annular velocity; Gy: Gray; HF: Heart failure; hsCRP: High-sensitivity C-reactive protein; IL-1: Interleukin-1; IQR: Interquartile range; LVEF: Left-ventricular ejection fraction; LVOT VTI CO: Left-ventricular outflow tract velocity time integral cardiac output; MCRD: Mean cardiac radiation dose Fig.…”
Section: Discussionmentioning
confidence: 99%